Rural Europe in Comparison: A SWOT Perspective on Quality of Life in the Selected Regions - Nikolić, Natalija; Krafková, Hana; Doulliez, Quentin; Svačina, Pavel; Presas-Basalo, Francisco Xose; Máté, Éva; Ptaček, Pavel (Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond, 2026)
Rural areas are diverse and different across the world, and they face numerous challenges, such as depopulation or economic and agricultural decline. The various faces of rural development describe a colourful composition of rural areas all over Europe, but according to experiences from separate research, some challenges are based on the same processes. However, the question remains whether European spatial planning policy on rural development can adopt a comparative approach in rural development, targeting the proper goals. In this paper, our aim was to evaluate the main characteristics of rural settlements in Wallonia (Belgium), Jihovýchod (the Czech Republic), Vojvodina (Serbia) and Galicia (Spain). Our goal was to find common opportunities for development by applying an assertive qualitative method, which can be used to prepare development goals. After a qualitative SWOT analysis of the common characteristics, the paper emphasises the importance of strengths and opportunities for rural development. The threats, such as climate change, increased demographic and economic decline and urban-rural polarisation, may be managed through adequate regional and rural planning.